ANTISIPASI RISIKO TERHADAP PETUGAS OPERASIONALALAT X-RAY DI BANDARA SULTAN AJI MUHAMMAD SULAIMAN SEPINGGAN BALIKPAPAN - Zulfikar, Iwan; Setyawati, Nur Falah; Saputra , Dharma; Nurfajri , Derry Andhika (Program Studi Kesehatan dan Keselamatan Kerja, 2023)
Industry and services at this time has used equipment or machines as well as hazardous materials used in daily work activities. One of the equipment or machines used by the aviation industry is X-ray aircraft by utilizing X-rays as a tool to detect passenger luggage. Since the discovery of X-rays in 1895 and then the production of radiographic equipment for the health and industrial fields, it has had a great impact on human life. This study aims to determine the level of occupational safety and health risk on X-ray equipment operational officers in the Security Check Point area. This research is a qualitative research and an assessment of health risks using the Health Risk Assessment (HRA) method. From the results of the study, there were 3 risks that could affect the health of workers, namely, inappropriate Personal Protective Equipment, room temperature and radiation exposure caused by the X-ray equipment. Therefore, it is necessary to have control by the company such as personnel monitoring tools, namely pocket dosimeters, film badges, TLD badges so that the dose received by each worker can be monitored.